Electrocardiogram (ECG) Signal Analysis and Feature Extraction: A Survey - Jagatap, Priyarani S; Jagtap, Rupali R (International Journal of Computer Sciences and Engineering, 2014)
ECG Signal plays an important role in the primary diagnosis, prognosis and survival analysis of heart diseases. ECG feature extraction plays an important role in the cardiac diseases. One cardiac cycle in an ECG signal consist of the P-QRS-T waves. It has amplitude and interval value which determines the functioning of heart of every human. ECG measures the rate and regularity of heartbeat. It displays the electrical activity of the heart in form of wave line on the paper. The ECG Signal is conducted with the data compression and reconstruction. Today so many research and techniques have been developed for analyzing the ECG signal. The information will then analyzed and classified on basis of compression method, fuzzy logic, etc.